2010
DOI: 10.1161/atvbaha.109.200303
|View full text |Cite
|
Sign up to set email alerts
|

Deficient CD4 + CD25 + T Regulatory Cell Function in Patients With Abdominal Aortic Aneurysms

Abstract: Objective-Increasing evidence shows that autoimmune response contributes importantly to pathogenesis of abdominal aortic aneurysm (AAA). This work was aimed to assess the possibly altered function of peripheral CD4 ϩ CD25 ϩ T regulatory cells (Tregs) that might breakdown immunologic self-tolerance in AAA patients. Methods and Results-Peripheral blood from 22 AAA patients, 11 patients with abdominal aortic atherosclerotic occlusive disease (AOD), and 32 healthy controls (HCs) was analyzed to determine the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 24 publications
4
64
0
3
Order By: Relevance
“…gd TCR + T cells also were clonally expanded in AAA lesions, and this includes the various forms of gd TCR + T cells previously reported (9,44). The frequency and the suppressor activity of CD4 + CD25 + FOXP3 + T cells in the pe- ripheral blood of patients with AAA were significantly lower versus with those in patients with abdominal aortic atherosclerotic occlusive disease or healthy donors (45). These results demonstrate impaired immunoregulation in AAA, which may play a role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 73%
“…gd TCR + T cells also were clonally expanded in AAA lesions, and this includes the various forms of gd TCR + T cells previously reported (9,44). The frequency and the suppressor activity of CD4 + CD25 + FOXP3 + T cells in the pe- ripheral blood of patients with AAA were significantly lower versus with those in patients with abdominal aortic atherosclerotic occlusive disease or healthy donors (45). These results demonstrate impaired immunoregulation in AAA, which may play a role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 73%
“…19,[25][26][27] Similarly, a recent clinical study has suggested that such an imbalance may also be involved in the pathogenesis of AAA and that expansion of Tregs could be a promising strategy to prevent AAA. 16 However, obstacles still remain for clinical applications such as cell-based therapy involving transfer of ex vivo expanded Tregs because of difficulties in separating pure Tregs and maintaining them stable after expansion on antigenic stimulation. Although other therapeutic approaches should be considered, no study has uncovered the effects of endogenous 17 Our recent study has shown that IL-2 complex treatment efficiently shifts the Treg/Teff balance toward Tregs, associated with its highly activated status, without affecting the Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs have been reported to exert beneficial effects on the progression of numerous diseases (9,10), including atherlerosclerosis (11), abdominal aortic aneurysms (12) and inflammatory bowel disease (13). However, the role of Tregs in the development of PAH remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%